Introducing the gender and market oriented agriculture workshop in Addis Ababa - Njuki, Jemimah; Puskur, Ranjitha (International Livestock Research Institute, 2011)
From 31 January to 2 February 2011, the International Livestock Research Institute (ILRI) hosts a workshop on gender and market oriented agriculture. Here, two of the meeting organizers - Jemimah Njuki and Ranjitha Puskur introduce the aims and anticipated outcomes of the workshop.